2020
DOI: 10.1016/j.cegh.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Confined vulnerability of HIV infection among pregnant women attending antenatal care clinics in Karnataka, India: Analysis of data from the HIV sentinel surveillance 2017

Abstract: Background: HIV Sentinel Surveillance among pregnant women attending antenatal care clinics, ANC-HSS, is used to estimate HIV prevalence among the general population. Despite the declining trend, HIV prevalence among the general population in Karnataka is still higher than the national average (0.22%), with a recent, noticeable stabilization. Demographic analysis on concentrated HIV infection among pregnant women could be potential indicators for targeted HIV interventions among general population as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…7,8 While spouse occupation being laborers, seasonal migration and commercial sex trade were associated with infection risks in North Karnataka, spouse occupation being truckers and transport workers were associated with infection risks in South Karnataka. 8,9 It is noteworthy that although no significant variation was observed in the overall urban-rural prevalence in Karnataka, HIV positivity in the recent rounds was comparatively higher in the rural areas (Table 3). In 2019, HIV prevalence in the rural sites ranged between 0.00% -2.13%, and the rural sites in Bangalore Rural (2.13%), Bijapur (0.77%), Belgaum (0.68%), Raichur (0.63%) Bagalkot (0.62%) and Davanagare (0.57%) recorded higher prevalence.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…7,8 While spouse occupation being laborers, seasonal migration and commercial sex trade were associated with infection risks in North Karnataka, spouse occupation being truckers and transport workers were associated with infection risks in South Karnataka. 8,9 It is noteworthy that although no significant variation was observed in the overall urban-rural prevalence in Karnataka, HIV positivity in the recent rounds was comparatively higher in the rural areas (Table 3). In 2019, HIV prevalence in the rural sites ranged between 0.00% -2.13%, and the rural sites in Bangalore Rural (2.13%), Bijapur (0.77%), Belgaum (0.68%), Raichur (0.63%) Bagalkot (0.62%) and Davanagare (0.57%) recorded higher prevalence.…”
Section: Discussionmentioning
confidence: 97%
“… 8 A previous study that analyzed the sociodemographic characteristics of HIV-positive pregnant women in Karnataka indicated that HIV was concentrated among pregnant women who were young and less educated, in their first gravida, residing in rural regions. 9 While the levels and trends of HIV prevalence at the national and state level are available, probing further into the region and district-wise levels and trends of HIV prevalence will provide critical insights on district-level epidemic patterns for region-specific tailor-made interventions. Hence, this paper analyzes the HSS data of pregnant women to derive the district-wise levels and trends of HIV prevalence in Karnataka.…”
Section: Introductionmentioning
confidence: 99%
“…Biological . Two studies used biological vulnerability in the context of maternal health: risk of comorbid anxiety and depression in pregnancy [ 31 ], and HIV positivity [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Of the included studies, 22 (34%) were publications on vulnerability in the context of maternal health; most studies focused on a single country, while two focused on multiple countries. The studies were conducted across 15 countries, four were from Brazil, and two from India, Pakistan and Chile [24][25][26][27][28][29][30][31][32][33].…”
Section: Vulnerabilities In Maternal Healthmentioning
confidence: 99%
“…In an effort to avoid HIV transmission from mother-to-child, knowing pregnant woman's HIV status enables her to initiate an urgent MTCT prevention program (PPIA). HIV counseling and testing are also included as a starting point in UNAIDS' approach for 'getting to zero' [1].…”
Section: Introductionmentioning
confidence: 99%